Use Of Olivine For The Production Of MgO-SiO2 Binders - Allan Nye, Scott; Vineet, Shah; Christopher, Oze; Barnaby, Shanks; Chris, Cheeseman (Frontiers in Built Environment, 2021)
The potential for using MgO and SiO2, recovered from olivine, was investigated for use as a cementitious binder system. The MgO to SiO2 proportion for the binder was fixed at 1:1. The nature of the hydration products were characterized using a variety of techniques including isothermal calorimetry, XRD, FTIR, and SEM. The primary binding component of the paste was determined to be magnesium silicate hydrate (M-S-H). The recovered silica exhibited faster reactivity compared to commercially available silica fume. Compressive strengths in excess of 20 MPa were obtained using the materials recovered from olivine.